Circannual variation in blood parasitism in a sub‐Saharan migrant passerine bird, the garden warbler. (26th April 2013) - Hellgren, O.; Wood, M. J.; Waldenström, J.; Hasselquist, D.; Ottosson, U.; Stervander, M.; Bensch, S.
Abstract Knowing the natural dynamics of pathogens in migratory birds is important, for example, to understand the factors that influence the transport of pathogens to and their transmission in new geographical areas, whereas the transmission of other pathogens might be restricted to a specific area. We studied haemosporidian blood parasites of the genera Plasmodium, Haemoproteus and Leucocytozoon in a migratory bird, the garden warbler Sylvia borin. Birds were sampled in spring, summer and early autumn at breeding grounds in Sweden, on migration at Capri, Italy and on arrival and departure from wintering staging areas in West Africa: mapping recoveries of garden warblers ringed in Fennoscandia and Capri showed that these sites are most probably on the migratory flyway of garden warblers breeding at Kvismaren. Overall, haemosporidian prevalence was 39%, involving 24 different parasite lineages. Prevalence varied significantly over the migratory cycle, with relatively high prevalence of blood parasites in the population on breeding grounds and at the onset of autumn migration, followed by marked declines in prevalence during migration both on spring and autumn passage. Importantly, we found that when examining circannual variation in the different lineages, significantly different prevalence profiles emerged both between and within genera. Our results suggest that differences in prevalence profiles are the result of either different parasite transmission strategies or coevolution between the host and the various parasite lineages. When separating parasites into common vs. rare lineages, we found that two peaks in the prevalence of rare parasites occur; on arrival at Swedish breeding grounds, and after the wintering period in Africa. Our results stress the importance of appropriate taxonomic resolution when examining host‐parasite interactions, as variation in prevalence both between and within parasite genera can show markedly different patterns.